Seeing Buildings Without Building Knowledge: How Laypeople Interpret Architectural Images in the Digital Age (Architecture Image Studies, 2026)
This study explores how everyday people perceive and interpret architectural images in our media-saturated world. Moving beyond traditional expert-focused research, it reveals a crucial shift toward understanding emotional and cultural responses from the general public. Using qualitative methods, the research shows non-experts rely on intuitive frameworks rather than formal design principles when evaluating buildings online. The research argues that architects and urban planners must integrate public perception into their work. This approach fosters inclusive communication and strengthens societal connection with architecture. Understanding how everyday people experience buildings in digital spaces creates opportunities for more meaningful, accessible design dialogue.